CSC 236 A1 2018 Winter

Download as pdf or txt
Download as pdf or txt
You are on page 1of 5

CSC236H, Fall 2017

Assignment 1
Sample Solutions

1. Prove by induction that 2n+2 + 32n+1 is divisible by 7 for all positive integers.
Solution:
P (n) : exists m ∈ N such that 2n+2 + 32n+1 = 7m.
We will prove that that P (n) hold for all natural numbers n.

Base Case: Assume n = 0.


Then we have 20+2 + 32∗0+1 = 22 + 3 = 7, which is indeed divisible by 7.

Induction Step: Let k be an arbitrary natural number. Assume that P (k) holds, i.e., exists m ∈ N
such that 2k+2 + 32k+1 = 7m. [IH]
We will show that P (k + 1) also holds.

2(k+1)+2 + 32(k+1)+1 = 2k+3 + 32k+3


= 2k+2 ∗ 2 + 32k+1 ∗ 32
= 2 ∗ (2k+2 + 32k+1 ) + 7 ∗ 32k+1
= 2 ∗ 7m + 7 ∗ 32k+1 # by IH
2k+1
= 7(2m + 3 )
0
= 7m # where m0 = 2m + 32k+1 and so m0 ∈ N

Thus P (k + 1) holds.
In conclusion, by the Principle of Simple Induction, P (n) hold for all natural numbers.
2. Consider the function: 
1,
 n=0
f (n) = 1, n=1
 √ 2 √
f (b nc) + 2f (b nc), n≥2

Use induction to prove that for all natural numbers n ≥ 4, f (n) is divisible by 5.

Solution: P (n) : There is some natural number i such that f (n) = 5i.
The goal is to prove that for all n ∈ N, n ≥ 4, P (n) holds.
√ √
Base Case: There are two base cases: (A) b kc = 2, and (B) b kc = 3.

1

Case A: Let b kc = 2. That is, k ∈ {4, 5, 6, 7, 8}.


f (k) = f (2)2 + 2f (2) # Since b kc = 2
= 32 + 2 ∗ 3 # Since f (2) = 3
= 15

Then f (k) = 5 ∗ 3, and so P (k) is true.



Case B: Let b kc = 3. That is, k ∈ {9, 10, 11, ..., 15}.


f (k) = f (3)2 + 2f (3) # Since b kc = 3
= 32 + 2 ∗ 3 # Since f (2) = 3
= 15

Then f (k) = 5 ∗ 3, and so P (k) is true.

Induction Step: Let k ∈ N and k ≥ 15. Suppose for all 4 ≤ j ≤ k, P (j) is true, i.e., f (j) = 5i for
some i ∈ N. [IH]
WTP: P(k+1) holds, i.e., f (k + 1) = 5i0 for some i0 ∈ N.
√ √
Notice that since k ≥ 15, we have√k + 1 ≥ 16, and so k + 1 ≥ 4. Thus we have b k + 1c ≥ 4.
Also, since k + 1 ≥ 16, we know k + 1 < k + 1.
By
√ the definition of the floor function
√ we have bxc ≤ x, for any real number x. So we √
can say that
b k + 1c < k + 1. Since both b k + 1c and k + 1 are natural numbers we can say that b k + 1c ≤ k.

√ 2 √
f (k + 1) = f (b k + 1c) + 2f (b k + 1c) # Since k + 1 ≥ 16 > 1
2
√ √
= (5m) + 2(5m) # Since 4 ≤ b k + 1c ≤ k, by IH we know that f (b k + 1c)

is divisible by 5, that is, for some m ∈ N, f (b k + 1c) = 5m
= 5(5m2 + 2m) # Factoring out 5
0
= 5m # where m0 ∈ N since N is closed under summation and multiplication

Thus, P (k + 1) is true.
Pn n(n+1)(2n+1)(3n2 +3n−1)
3. Prove using the Well Ordering Principle that k=1 k4 = 30 .
Solution: Pn 2
Let P (n) denote k=1 k 4 = n(n+1)(2n+1)(3n
30
+3n−1)
.
We want to prove that for all n ∈ N, n ≥ 1, P (n) holds.

For a contradiction, assume that there is some m ∈ N, m ≥ 1, such that P (m) does not hold.
Let C be the set of all natural numbers greater that 0 for which the predicate does not hold, i.e.,
n
X n(n + 1)(2n + 1)(3n2 + 3n − 1)
C = {n ∈ N|n ≥ 1 and k 4 6= }.
30
k=1

By our assumption C is not empty. By definition, C is a subset of N.


By PWO there exists a smallest element a in C.

2
1 is not in C, as the formula is verified for 1.
Then a > 1, and so a − 1 ≥ 1. That is a − 1 ∈ N.
Since a − 1 < a and a is the minimum element of C, a − 1 6∈ C, i.e.,
a−1
X (a − 1)a(2(a − 1) + 1)(3(a − 1)2 + 3(a − 1) − 1)
k4 = .
30
k=1

Expanding the right hand side of the formula we get that


a−1
X (a − 1)a(2a − 1)(3(a2 − 2a + 1) + 3a − 2)
k4 =
30
k=1
a(a − 1)(2a − 1)(3a2 − 6a + 3 + 3a − 2)
=
30
a(2a2 − 3a − 1)(3a2 − 3a + 1)
=
30
a(6a4 − 15a3 + 10a2 − 1)
=
30
Adding a4 to both sides we get
a−1
X a(6a4 − 15a3 + 10a2 − 1)
k 4 + a4 = + a4
30
k=1
a(6a4 + 15a3 + 10a2 − 1)
=
30
which in turn can be rewritten as
a
X a(6a4 + 15a3 + 10a2 − 1)
k4 =
30
k=1

On the other hand, if we expand (a+1)(2a+1)(3a2 +3a−1) we can see that (a+1)(2a+1)(3a2 +3a−1)
is equal to a(6a4 + 15a3 + 10a2 − 1). That is
a
X a(6a4 + 15a3 + 10a2 − 1)
k4 =
30
k=1
(a + 1)(2a + 1)(3a2 + 3a − 1)
=
30
which implies that P (a) holds and so a 6∈ C.
This contradicts our assumption that a is the minimal element of C.
Thus we conclude that our assumption is false. That is, for all n ∈ N
n
X n(n + 1)(2n + 1)(3n2 + 3n − 1)
k4 = .
30
k=1

4. Let L : Z2 → N be a function defined by the equation

L(x, y) = x2 + y 2 .

Let C ⊆ Z2 be the smallest set such that:

3
• (1, 1), (−1, 1) ∈ C.
• If (r, s), (t, u) ∈ C then (r, −s), (rt − su, ru + st) ∈ C.
Use induction to prove that for any (x, y) ∈ C, L(x, y) is a power of 2.

Solution: Proof by structural induction on the structure of C.

P (x, y) : There is some k ∈ N such that L(x, y) = 2k .

Base Case: There are 2 cases (A) (x, y) = (1, 1) and (B) (x, y) = (1, −1).

Case A: Suppose (x, y) = (1, 1).


Then L(x, y) = 12 + 12 = 2 = 21 .
So L(x, y) is a power of 2.

Case B: Suppose (x, y) = (−1, 1).


Then L(x, y) = (−1)2 + 12 = 2 = 21 .
So L(x, y) is a power of 2.

Induction Step: Suppose (r, s), (t, u) ∈ C.


Assume that P(r,s) and P(t,u) hold. That is:
There are some i, j ∈ N such that r2 + s2 = 2i and t2 + u2 = 2j . [IH]
WTP: P (x, y) holds for (A) (x, y) = (r, −s) and (B) (x, y) = (rt − su, ru + st).

Case A: Suppose (x, y) = (r, −s). Then

L(x, y) = r2 + (−s)2 # definition of L


2 2
=r +s # since (−s)2 = s2
= 2i . # by IH

So L(x, y) is a power of 2, and P (x, y) holds.

Case B: Suppose (x, y) = (rt − su, ru + st). Then

L(x, y) = (rt − su)2 + (ru + st)2 # definition of L


= (rtrt − 2rtsu + susu) + (ruru + 2rust + stst) # expand terms
= rtrt + susu + ruru + stst # -2rtsu cancels +2rust
2 2 2 2
= (r + s ) ∗ (t + u ) # factor into product of sums
i j
=2 ∗2 # by IH
i+j
=2 .

So L(x, y) is a power of 2, and P (x, y) holds.

5. Let  denote the empty string, and Σ be a set of characters. The reversal of a string w, denoted wR ,
can be defined recursively as follows:

• R = ;

4
• If w = ua for some string u composed of characters in Σ and some character a ∈ Σ, then
wR = auR .
Use structural induction to prove that for all strings w composed of characters in Σ, (wR )R = w.

You may use the following fact, which is proved in the CSC236/240 Course Notes:
For all strings u, w, (wu)R = uR wR .
Solution: P (w) : (wR )R = w.

Base Case: Let w = .


Then applying the base case of the recursive definition twice, (wR )R = (R )R = ()R =  = w.

Induction Step: Let w = ua where u is a string composed of characters in Σ and a ∈ Σ.


Assume P (u). [IH]

WTP: P (w) holds.

Case 1: Assume u is the empty string, that is, u = .


Then

wR = ( · a)R
= a · R # by the recursive rule
=a· # by the base rule
=a # by properties of .
=w

Hence (wR )R = wR = w.
Notice also that w =  · a = a, and so we just showed for an arbitrary character a ∈ Σ, aR = a.

Case 2: Assume u is not the empty string.


Then,

(wR )R = ((ua)R )R = (a · uR )R # by the recursive rule


R R R
= (u ) · a # by the fact
R
= ua # by the induction hypothesis
= ua # as proved in Case 1
= w.

You might also like